ANALISIS PENERAPAN KONSERVATISME AKUNTANSI DI INDONESIA DALAM PERSPEKTIF POSITIVE ACCOUNTING THEORY - Nutfi Rizki Hertina; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2017)
This study aims to analyze the application of accounting conservatism in positive accounting theory perspective that consist of bonus plan hypothesis, debt covenant hypothesis, and political cost hypothesis. This study used sample that consist of 136 manufacturing companies listed on Indonesia Stock Exchange in 2011-2014. Samples of this study were selected by purposive random sampling method with certain criteria. The analysis technique used is multiple regression. The result show that the managerial ownership, public ownerships, and capital intensity have no significant effect to accounting conservatism. Leverage has positive effect to acccounting conservatism, while the firm size has negative effect to accounting conservatism. Based on the results concluded that, accounting conservatism is affected by leverage and firm size.